Translating the transition: the translator-detective in Post-Soviet fiction - Baer, Brian James (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article explores the ways in which the figure of the translator-detective in contemporary Russian literature functions to express and neutralize a range of fears and anxieties engendered by the post-Soviet transition. Tracing the roots of the motif of the translator in Russian literature back to F. M. Dostoevsky ’s Crime and Punishment, the paper then examines the translator-hero in the detective fiction of the best-selling contemporary authors Aleksandra Marinina, Boris Akunin, Dar’ia Dontsova, and Polina Dashkova. Representatives of the embattled Russian intelligentsia, their translator-detectives embody resistance to mindless cultural borrowing from the West.